Pertumbuhan Akar Kedelai pada Cekaman Aluminium, Kekeringan dan Cekaman Ganda Aluminium dan Kekeringan - HANUM, CHAIRANI; MUGNISJAH, WAHYU Q.; YAHYA, SUDIRMAN; SOPANDY, DIDI; IDRIS, KOMARUDIN; SAHAR, ASMARLAILI (AGRITROP; Vol. 26, No. 1 Maret 2007)
The objective of this research was to study the change of vegetative growth of root on some genotypes soybean of aluminium toxicity, drought stress, and double stress (Al toxicity and drought stress). Research in rooting system of soybean is hoped to get more attention, especially for supporting concept of new plant type for high yielding potential. Six genotypes of soybean (Slamet, Sindoro, Dieng, Sinyonya, Lumut, and Wilis), treated with aluminium saturated (Al 25%, Al 50%, and Al 75%) and field capacity (80% FC and 40% FC). Response of growth vegetative identified perception by root dry weight. Result of the study show that only one from six that is genotype Wilis was tolerant at aluminium toxicity, drought stress, and double stress.
Keywords: soybean, Al toxicity, drought stress, double stress, tolerant.